AKTIVITAS ANTIMIKROBA EKSTRAK METANOL BIJI MANGGA HARUM MANIS (Mangifera indica L. Varietas Arumanis 143) TERHADAP Bacillus subtilis dan Shigella flexneri - Rachmatiah, Tiah; Poeloengan, Masniari; Pratama, Helgario (Sainstech Farma: Jurnal Ilmu Kefarmasian, 2020)
Antimicrobial activity of methanol extract from harum manis mango seeds (Mangifera indica L.varietas Arumanis 143) has been investigated against Bacillus subtilis and Shigella flexneri. Harum manis mango seeds powder were extracted with methanol by maceration method Phytochemical screening of the extract indicated that the extract contained flavonoids, saponins and tannins. Antimicrobial activity of the extracts were tested against Bacillus subtilis and Shigella flexneri with amoxicillin as a positive control. Diffusion and dilution methods by using Mueller-Hinton medium.were used in this test. The results exhibited tha tzone diameters of inhibition of 50% extract solution in water against B.subtilis and S.flexneri were respectively 18 mm and 17 mm. The Minimum Inhibitory Concentration (MIC) values against B. subtilis and S. flexineri were showed respectively at 0.3% and 3% extract solutions of harum manis mango seeds.